Prostacyclin Analogue Beraprost Inhibits Cardiac Fibroblast Proliferation Depending on Prostacyclin Receptor Activation through a TGF β-Smad Signal Pathway - Chen, Yun; Yang, Shengju; Yao, Wenjuan; Zhu, Hongyan; Xu, Xiaole; Meng, Guoliang; Zhang, Wei (PLOS ONE, 2014)
Previous studies showed that prostacyclin inhibited fibrosis. However, both receptors of prostacyclin, prostacyclin receptor (IP) and peroxisome proliferator-activated receptor (PPAR), are abundant in cardiac fibroblasts. Here we investigated which receptor was vital in the anti-fibrosis effect of prostacyclin. In addition, the possible mechanism involved in protective effects of prostacyclin against cardiac fibrosis was also studied. We found that beraprost, a prostacyclin analogue, inhibited angiotensin II (Ang II)-induced neonatal rat cardiac fibroblast proliferation in a concentration-dependent and time-dependent manner. Beraprost also suppressed Ang II-induced collagen I mRNA expression and protein synthesis in cardiac fibroblasts. After IP expression was knocked down by siRNA, Ang II-induced proliferation and collagen I synthesis could no longer be rescued by beraprost. However, treating cells with different specific inhibitors of PPAR subtypes prior to beraprost and Ang II stimulation, all of the above attenuating effects of beraprost were still available. Moreover, beraprost significantly blocked transforming growth factor β (TGF β) expression as well as Smad2 phosphorylation and reduced Smad-DNA binding activity. Beraprost also increased phosphorylation of cAMP response element binding protein (CREB) at Ser133 in the nucleus. Co-immunoprecipitation analysis revealed that beraprost increased CREB but decreased Smad2 binding to CREB-binding protein (CBP) in nucleus. In conclusion, beraprost inhibits cardiac fibroblast proliferation by activating IP and suppressing TGF β-Smad signal pathway.